The Conditions of Governance for the Implementation of the Nationalally Determined Contributions: The case of Peru - Lanegra, Ivan (2018)
This paper proposes a framework of analysis for the governance dimension in the implementation in Peru of the Nationally Determined Contributions derived from the Paris Agreement (NDC). The less developed countries, such as the one mentioned, add to the technological and financing difficulties to implement the NDC, the institutional weaknesses. In this context, the analysis of governance conditions should consider short-term political factors, constraints on institutional development, as well as elements of political economy. This leads us to consider both the sectoral and territorial dynamics, as well as the different roles that actors, with economic and political power, play around climate policy.